PEMANFAATAN MEDIA SOSIAL OLEH ORANG MUDA KATOLIK DALAM PEWARTAAN IMAN: PERSPEKTIF DOKUMEN CHRISTUS VIVIT - Ubania Simanjuntak; Petrus Simarmata (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was designed to map the extent to which Catholic Youth utilize social media as a vehicle for faith proclamation, while simultaneously evaluating whether such practices align with the evangelization spirit upheld in the document Christus Vivit. Data collection centered on the Catholic Youth community at the Parish of Saint Francis of Assisi Pangaribuan, with a qualitative approach grounded in case study methodology as its methodological framework. Information was gathered through three simultaneous channels field observation, in-depth interviews, and documentation review involving ten young people as primary informants, supported by a youth mentor and the parish priest. The collected data was then processed through a series of stages: reduction, presentation, and conclusion drawing, with triangulation employed as an instrument to ensure validity. The findings reveal a striking paradox: the high intensity of social media use among young people does not proportionally translate into its optimization as a space for faith proclamation, digital catechesis, or the expression of social solidarity the utilization of social media for such purposes remains sporadic and far from consistent. From this, the study concludes that a considerable gap exists between habitual social media engagement and awareness of its function as a medium for evangelization. Bridging this gap requires a formation program that is not only substantively directed, but also designed to operate over the long term. ABSTRAK Penelitian ini dirancang untuk memetakan sejauh mana Orang Muda Katolik menggunakan media sosial sebagai wahana penyebaran iman, sekaligus mengevaluasi apakah praktik tersebut sejalan dengan semangat evangelisasi yang diusung dokumen Christus Vivit. Pengambilan data berpusat pada komunitas Orang Muda Katolik di Paroki Santo Fransiskus Asisi Pangaribuan, dengan pendekatan kualitatif berbasis studi kasus sebagai kerangka metodologisnya. Proses penggalian informasi ditempuh melalui tiga jalur sekaligus pengamatan lapangan, wawancara mendalam, dan telaah dokumentasi yang melibatkan sepuluh orang muda sebagai informan utama, didukung oleh seorang pembina dan pastor paroki. Data yang terkumpul kemudian diolah lewat serangkaian tahapan: penyaringan, pemaparan, dan penarikan kesimpulan, dengan triangulasi sebagai instrumen penjamin keabsahan. Hasil yang diperoleh mengungkap paradoks yang menarik: tingginya intensitas penggunaan media sosial di kalangan orang muda tidak berbanding lurus dengan optimalisasi fungsinya sebagai ruang pewartaan iman, katekese digital, maupun ekspresi solidaritas sosial pemanfaatan untuk tujuan-tujuan tersebut masih berlangsung sporadis dan jauh dari kata konsisten. Dari sini, penelitian menyimpulkan adanya jurang pemisah antara kebiasaan bermedia sosial dan kesadaran akan fungsinya sebagai medium evangelisasi. Menutup jurang tersebut membutuhkan program pembinaan yang tidak hanya terarah secara substansi, tetapi juga dirancang untuk berjalan dalam jangka panjang.